A STUDY OF PREVIEWING AND PREDICTING STRATEGY IN TEACHING READING COMPREHENSION AT SMP NEGERI 14 SIGI - Windi Putri Anggraini; Sriati Usman; Muhammad Arid (Tadulako University, 2022)
The Previewing and Predicting Strategy were strategy that applied by teacher in teaching reading comprehension during class. The objective of this research was to find out the implementation of Previewing and Predicting Strategy in teaching reading comprehension at SMA Negeri 14 Sigi. This research was conducted by used descriptive qualitative research were taken from the English teacher at SMA Negeri 14 Sigi as subject of the research. The data of this research was collected from the interview of the English teacher. This research was used an interview guide as the instrument of the collected data. Based on the data obtained was concluded that in the implemented of previewing and predicting strategy in teaching reading comprehension at SMA Negeri 14 Sigi was effective. In the implementation of the previewing and predicting strategy in teaching reading comprehension, the English teacher had challenged such as: students’ lack of vocabulary, students’ difficult of text comprehend, learning material were only supported by text, time of implementation, and students’ needed of clear instruction.